Analysis Of Marketing Strategy Non-Profit Organization the International Center For Awqaf Studies (ICAST) In Gontor Ponorogo - Kurniawan, Dhika Amalia; Arius, Febri; Ramadhani, Muhammad Rizky (Universitas Nusantara PGRI Kediri, 2024)
Research aim :This research aims to formulate a marketing strategy for a non-profit institution, namely the International Center for Awqaf Studies (ICAST), in its operations as an institution that provides waqf education to the wider community. Design/Methode/Approach :Data collection used a qualitative approach, data collection used observation, interview and documentation techniques and data analysis used was descriptive analysis techniques. Research Finding : The results of the research show that the ICAST institution needs to take advantage of the opportunities and strengths it has to develop a marketing strategy for ICAST to the wider community, and strategies are also needed for each component of the advertising mix indicators, even though ICAST is an institution that does not aim to make a profit, a marketing strategy is needed to be able to carry out The goal of the organization is to provide knowledge. and educating the public about the importance of waqf in social life. Theoretical contribution/Originality :This research provides theoretical contributions regarding marketing strategy in the context of non-profit organizations Practitionel/Policy implication :The results of this research can be utilized by non-profit institutions to carry out marketing in their non-profit activities so that they can be of interest to the wider community in their operations of providing waqf education to all levels of society. Research limitation :This research is still limited to one object of non-profit institutions engaged in waqf education, it is not comprehensive in other non-profit institutions, so further research is needed in other non-profit organizations.